Actinidin diversity: discovery of common and selective substrates for actinidin isoforms and Actinidia cultivars. Issue 36 (30th August 2022) - Martin, Harry; Simpson, Robert M.; Seal, Alan; Chen, Ronan; Hedderley, Duncan
Abstract : The actinidin proteinase family has a striking sequence diversity at the active site. Abstract : The actinidin proteinase family has a striking sequence diversity; isoelectric points range from 3.9 to 9.3. The biological drive for this variation is thought to be actinidin's role as a defense-related protein. In this study we map mutations in the primary sequence onto the 3D structure of the protein and show that the region with the highest diversity is close to the substrate binding groove. Non-conservative substitutions in the active site determine substrate preference and therefore create problems for quantification of actinidin activity. Here we use a peptide substrate library to compare two actinidin isoforms, one from the kiwiberry cultivar 'Hortgem Tahi' ( Actinidia arguta ), and the other from the familiar kiwifruit cultivar 'Hayward' ( Actinidia chinensis var. deliciosa ). Among 360 octamer substrates we find one substrate (RVAAGSPI) with the useful property of being readily cleaved by all the functionally active actinidins in a set of A. arguta and A. chinensis var. deliciosa isoforms. In addition, we find that two substrates (LPPKSQPP & ILRDKDNT) have the ability to differentiate different isoforms from a single fruit. We compare actinidins from 'Hayward' and A. arguta for their ability to digest the allergenic gluten peptide (PFPQPQLPY) but find the peptide to be indigestible by all sources of actinidin. The ability to inactivate salivary amylase is shown to be a common trait in Actinidia cultivars due to proteolysis by actinidin and is particularly strong in 'Hortgem Tahi'. A mixture of 10% 'Hortgem Tahi' extract with 90% saliva inactivates 100% of amylase activity within 5 minutes. Conceivably, 'Hortgem Tahi' might lower the glycaemic response in a meal rich in cooked starch.